Delineation of Self Image: A Critical Study of Perception in Autistic Children - Verma, Charu; Arora, Manavpreet Kaur (International Journal of Psychosocial Rehabilitation, 2020)
Autism spectrum disorder or ASD is a neurodevelopmental disorder and individuals suffering with it face social and communicative difficulties. Many of them show mismatched Lovely Professional University, Phagwara, Punjab, India.feelings about themselves. The current study focuses on the perception of children with ASD about themselves and their immediate awareness of the environment. The main objective of this research is to decipher their conceptual understanding about themselves as well as focus on their observation skills and their artistic qualities in expressing their perception through the medium of art. It is a qualitative research which utilizes random sampling method to analyze a group consisting of 6 autistic children, 3 male and 3 female; belonging to the age group of 6-12 years. The experiment required them to make a self-portrait wherein they were given instructions about the activity and supervised. Results show that most autistic children struggle with representation of self though they are sensitive to certain details of their body. The notion of self is extended to immediate environment as well as belongings. Drawing of form rather than color is the primary medium for expression of feelings.